My Math Forum Solve the problem in ratio

 Algebra Pre-Algebra and Basic Algebra Math Forum

 January 21st, 2010, 12:06 AM #1 Newbie   Joined: Dec 2009 Posts: 3 Thanks: 0 Solve the problem in ratio How do I do this? 1. If a/b = c/d = e/f Show that: ( 2(a^4)(b^2) + 3(a^2)(e^2) -5(e^4)(f) ) / ( 2(b^6) + 3(b^2)(f^2) -5(f^5) ) = (a^4)/(b^4)
 January 21st, 2010, 01:40 AM #2 Global Moderator   Joined: Dec 2006 Posts: 21,020 Thanks: 2255 a/b = e/f implies e² = a²f²/b², so 2(a^4)b² + 3a²e² - 5(e^4)f = 2(a^4)b² + 3(a^4)f²/b² - 5(a^4)(f^5)/b^4                                               = (a^4/b^4)(2b^6 + 3b²f² - 5f^5), etc. What happens if b = f = 1?
 January 21st, 2010, 03:05 AM #3 Newbie   Joined: Dec 2009 Posts: 3 Thanks: 0 Re: Solve the problem in ratio thanks for the answer, it's quite simple, but never realized it.

 Tags problem, ratio, solve

 Thread Tools Display Modes Linear Mode

 Similar Threads Thread Thread Starter Forum Replies Last Post extjsjquery Algebra 1 December 9th, 2013 09:52 AM jon619 Algebra 2 October 1st, 2013 01:12 PM homeschooling Elementary Math 2 June 5th, 2013 03:34 PM angelina Elementary Math 4 August 8th, 2010 11:58 PM piggysmile Algebra 4 May 31st, 2010 03:41 AM

 Contact - Home - Forums - Cryptocurrency Forum - Top